Democracy's Violent Birth: The Czech Legionnaires and Statue Wars in the First Czechoslovak Republic. (May 2022) - Wingfield, Nancy M.
Abstract : "Oh, home of tears, but let her bear this blazoned to the end of time: No nation rose so white and fair, none fell so pure of crime." So reads the stanza from a poem popular in the South during the Civil War engraved on a Confederate soldier statue unveiled in 1911 on the lawn of the Cooke County courthouse in Gainesville, Texas (Figure 1). It is one of two Confederate statues long on display in the city of some 16, 000 some ninety miles north of Dallas. This larger-than-life soldier, standing high upon a column, towers over an important public space. It is among many Confederate monuments that long occupied public spaces across the United States, often with little local debate, despite their often white-supremacist inscriptions.